2010
DOI: 10.4310/cag.2010.v18.n5.a5
|View full text |Cite
|
Sign up to set email alerts
|

Slow convergence of graphs under mean curvature flow

Abstract: In loving memory of my mother Zahida Perveen ErklärungIch bestätige hiermit, dass ich diese Arbeit selbständig verfasst und keine anderen als die angegebenen Hilfsmittel und Quellen verwendet habe. Kashif RasulTag der mündlichen Qualifikation: 27. Januar 2010 1. Gutachter: Prof. Dr. Klaus Ecker 2. Gutachterin: Dr. Maria Athanassenas AbstractIn this thesis we study the mean curvature flow of entire graphs in Euclidean space. From the work of Ecker and Huisken, we know that given some initial growth condition at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
(25 reference statements)
0
4
0
Order By: Relevance
“…As in the case of the mean curvature flow, see [9,16,19], it turns out that M t moves out to infinity as time increases, and that it converges to a smooth limit after an appropriate rescaling. As in [9], the convergence of the rescaled flow will be proved under an additional assumption on the initial value which controls the possible oscillations at infinity: there exist constants 0 < δ < 1 and K 0 > 0 such that…”
Section: Asymptotic Behaviourmentioning
confidence: 81%
See 2 more Smart Citations
“…As in the case of the mean curvature flow, see [9,16,19], it turns out that M t moves out to infinity as time increases, and that it converges to a smooth limit after an appropriate rescaling. As in [9], the convergence of the rescaled flow will be proved under an additional assumption on the initial value which controls the possible oscillations at infinity: there exist constants 0 < δ < 1 and K 0 > 0 such that…”
Section: Asymptotic Behaviourmentioning
confidence: 81%
“…The same authors [10] showed that global time existence holds for any initial data which is an entire graph over R n , regardless of its growth. After this, Stavrou [19] proved the convergence to a selfsimilar profile of Lipschitz graphs having a unique cone at infinity, while Rasul [16] obtained a convergence result under a weaker oscillation condition than in [9]. The long time behaviour without rescaling has been investigated for special classes of solutions: Clutterbuck, Schnürer and Schulze [8] have proved stability of translating solutions of the graphical mean curvature flow, while Clutterbuck and Schnürer [7] have considered the stability of mean convex cones.…”
Section: ∂F ∂T (P T) = −S (P T) ν (P T)mentioning
confidence: 99%
See 1 more Smart Citation
“…Later Stavrou [32] proved such a result under the weaker assumption that the initial hypersurface attains a unique tangent cone at infinity. Rasul [25] showed that under an alternative condition at infinity and bounded gradient, the rescaled graphs converge to self-similar solutions but at a slower speed. Clutterbuck and Schnürer [5] considered graphical solutions to mean curvature flow and obtained a stability result for homothetically expanding solutions coming out of cones of positive mean curvature.…”
Section: Introductionmentioning
confidence: 99%